2019
DOI: 10.4028/www.scientific.net/kem.822.634
|View full text |Cite
|
Sign up to set email alerts
|

Technological Principles of Internal Surfaces Finishing by Forced Electrolytic-Plasma Polishing

Abstract: Technological difficulties of manufacture, typical to the large number of crucial elements of certain assemblies: tubes of fuel systems, details of waveguide devices, smooth gun barrels and other tubular details. Difficulties associated with the finishing of the internal surfaces of these products. Therefore, great interest is to find a finishing technology, which allow processing such products. The kind of electrolytic-plasma polishing technology - forced electrolytic-plasma polishing (FEPP) allows to receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Yuan and other scholars used the spiral rotating abrasive flow polishing technology to precisely polish the inner surface of the 6061 aluminum alloy cylinder, and the research results showed that the technology significantly improved the polishing efficiency and uniformity [7]. Radkevich and other scholars used the forced electrolytic plasma polishing (FEPP) method to machine the inner surface of the tubular workpiece and obtained a uniform surface [8]. Tyagi and other scholars have studied electropolishing and chemical polishing methods to reduce the surface roughness of the inner surface.…”
Section: Introductionmentioning
confidence: 99%
“…Yuan and other scholars used the spiral rotating abrasive flow polishing technology to precisely polish the inner surface of the 6061 aluminum alloy cylinder, and the research results showed that the technology significantly improved the polishing efficiency and uniformity [7]. Radkevich and other scholars used the forced electrolytic plasma polishing (FEPP) method to machine the inner surface of the tubular workpiece and obtained a uniform surface [8]. Tyagi and other scholars have studied electropolishing and chemical polishing methods to reduce the surface roughness of the inner surface.…”
Section: Introductionmentioning
confidence: 99%